Inorganic Mediator toward Organosulfide Active Material: Anchoring and Electrocatalysis. (26th June 2020) - Fan, Qianqian; Guo, Wei; Si, Yubing; Wang, Xin; Wang, Bo; Fu, Yongzhu
Abstract: Organosulfides are promising high‐capacity cathode materials for rechargeable lithium batteries. However, they are hindered by several key challenges including the electronic/ionic insulation and solubility issues of the discharged products. Herein, TiS2 nanosheets@carbon nanotubes (TiS2 NSs@MWCNT) are proposed as a promoter and booster toward phenyl tetrasulfide (PTS). It serves as a bifunctional mediator, not only anchoring active materials in the cathode through chemical adsorption but also facilitating the reaction kinetics. The Li‐organosulfide cell yields a reversible discharge capacity of 467.6 mAh g −1 and a high capacity retention of 81.9% after 200 cycles at 0.5 C rate. When the PTS areal mass loading is 5.8 mg cm −2 and the electrolyte/PTS ratio is 3.8 µL mg −1, a high specific capacity of 444 mAh g −1 at 0.5 C rate can still be achieved. The strong anchoring and electrocatalysis effects of TiS2 toward PhSLi and polysulfide are revealed using experimental and computational approaches. The study sheds light on metal sulfides as mediators to improve the cycling life of Li‐organosulfide batteries and provides deep comprehension of the instinct interaction evolution at molecular level, which is invaluable for fabrication of electrode materials. Abstract : TiS2 nanosheets are used as a promoter and booster toward a phenyl tetrasulfide cathode. It serves as a bifunctional mediator, not only anchoring active materials in the cathode through chemical adsorption but also facilitating the reaction kinetics leading to stable cycle life.